2018
DOI: 10.1155/2018/7270127
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness in Chinese Children Aged 8 to 11 Years with Mild and Moderate Myopia

Abstract: Purpose To investigate macular choroidal thickness (CT), topographical variation, and associations between subfoveal choroidal thickness (SFCT) and age, gender, spherical equivalent (SE), and axial length (AL) in Chinese healthy mild and moderate myopia children aged 8 to 11 years. Methods One hundred twenty eyes from 120 healthy children were studied. Children were divided into mild and moderate myopia groups. AL and CT were evaluated. CTs were measured at the fovea, and 1 mm, 2 mm, and 3 mm nasal, temporal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 30 publications
5
15
3
Order By: Relevance
“…Studies from various parts of world have evaluated different normal SFCT values for different ethnic groups like 249.6 (SD ± 36) μm in Indians[ 6 ] and 252.80 (SD ± 46.95) μm in Chinese. [ 7 ] We here observed the mean SFCT in the unaffected fellow eye to be 251 ± 66.38 μm which can be considered as the SFCT of healthy Nepalese population.…”
Section: Discussionmentioning
confidence: 59%
“…Studies from various parts of world have evaluated different normal SFCT values for different ethnic groups like 249.6 (SD ± 36) μm in Indians[ 6 ] and 252.80 (SD ± 46.95) μm in Chinese. [ 7 ] We here observed the mean SFCT in the unaffected fellow eye to be 251 ± 66.38 μm which can be considered as the SFCT of healthy Nepalese population.…”
Section: Discussionmentioning
confidence: 59%
“…The notable difference could be attributed to the more intensive pre-school education, along with frequent near-work activities and lack of outdoor time due to crowded living places in Hong Kong compared to other regions of China 22 . Given the widely accepted postulation of the negative relationship between choroidal thickness and myopia 26 , 35 , it is conceivable that the measured choroid is thinner in our study population.…”
Section: Discussionmentioning
confidence: 92%
“…Enhanced depth imaging optical coherence tomography (EDI-OCT) has the capacity to image the choroid in vivo with enhanced visualization of the choroidal anatomy and choroidal thickness measurement [7,8]. Using this technology, previous studies have found topographic variations of the choroid, and that CT is significantly thinner in myopic eyes than in emmetropic eyes [9][10][11][12][13]. Previous studies have also investigated the relationships between CT and other ocular or systemic variables [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Using this technology, previous studies have found topographic variations of the choroid, and that CT is significantly thinner in myopic eyes than in emmetropic eyes [9][10][11][12][13]. Previous studies have also investigated the relationships between CT and other ocular or systemic variables [11,14,15]. Sevaral factors, including age, refractive error and axial length (AL), have been consistently identified to be associated with CT among healthy adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation